Implementasi Program Kerja Kampus Mengajar Dalam Meningkatkan Literasi, Numerasi Di Sdn Sukolilo 250, Surabaya, Jawa Timur - Maria Yuliana Postel; Cholis Hidayati (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2023)
The teaching campus program is part of the independent campus program which has an important contribution to the advancement of education in Indonesia, where students from teaching campuses will be placed in various assigned schools with the main target of this program being Elementary Schools (SD) and Junior High Schools located in the region. 3T (Left behind, Outermost, and Forefront) which will then assist educators in schools in the learning process and assist schools in improving literacy, numeracy, and technology adaptation.This study aims to determine the role of teaching campus students in helping improve literacy and numeracy at SDN Sukolilo 250, Surabaya, East Java in order to improve the quality of education in Indonesia. The type of research used is descriptive qualitative, with a research time of 6 months. The location of this research was at SDN Sukolilo 250, Surabaya, East Java. As for the techniques and instruments used in collecting data using interview techniques, observation, and documentation. Based on this research, it can be concluded that campus teaching campus students have an important role in increasing literacy, numeracy in schools.